Seasonal home range dynamics and sex differences in habitat use in a threatened, coastal marsh bird - Kolts, Jaan Runyon; McRae, Susan B. (My University, 2016)
A comprehensive understanding of spatiotemporal ecology is needed to develop conservation strategies for declining species. The king rail (Rallus elegans) is a secretive marsh bird whose range historically extended across the eastern United States. Inland migratory populations have been greatly reduced with most remaining populations inhabiting the coastal margins. Our objectives were to determine the migratory status of breeding king rails on the mid-Atlantic coast and to characterize home range size, seasonal patterns of movement, and habitat use. Using radiotelemetry, we tracked individual king rails among seasons, and established that at least a segment of this breeding population is resident. Mean (±SE) home range size was 19.8 ± 5.0 ha (95% kernel density) or 2.5 ± 0.9 (50% kernel density). We detected seasonal variation and sex differences in home range size and habitat use. In the nonbreeding season, resident male home ranges coincided essentially with their breeding territories. Overwintering males were more likely than females to be found in natural emergent marsh with a greater area of open water. Females tended to have larger home ranges than males during the nonbreeding season. We report for the first time the use of wooded natural marsh by overwintering females. Brood-rearing king rails led their young considerable distances away from their nests (average maximum distance: ~600 ± 200 m) and used both wooded natural and impounded marsh. King rails moved between natural marsh and managed impoundments during all life stages, but the proximity of these habitat types particularly benefitted brood-rearing parents seeking foraging areas with shallower water in proximity to cover. Our results demonstrate the importance of interspersion of habitat types to support resident breeders. Summer draining of impounded wetlands that are seasonally flooded for wintering waterfowl allows regrowth of vegetation and provides additional habitat at a critical time for wading birds.
Keywords: coastal ecology; conservation; habitat preference; impoundment; radiotelemetry; Rallidae; Rallus elegans; seasonality; sexual segregation; wetland